Daily field checking list by Walter Rosene, April 26, 1932 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated April 26, 1932. This checklist was used by Walter Rosene to record birds sighted around North Bridge with Bob Walker between 6:40 and 9:10. Plustek--flatbed